2021
DOI: 10.3390/pathogens10030346
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gametocytes of the Malaria Parasite Plasmodium falciparum in a Functional Genomics Era: Next Steps

Abstract: Mosquito transmission of the deadly malaria parasite Plasmodium falciparum is mediated by mature sexual forms (gametocytes). Circulating in the vertebrate host, relatively few intraerythrocytic gametocytes are picked up during a bloodmeal to continue sexual development in the mosquito vector. Human-to-vector transmission thus represents an infection bottleneck in the parasite’s life cycle for therapeutic interventions to prevent malaria. Even though recent progress has been made in the identification of geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 235 publications
(169 reference statements)
0
20
0
1
Order By: Relevance
“…Indeed, the enormous complexity of this overall system has led to new efforts utilizing mathematical and computational modelling strategies to study the problems and trajectories [ 172 174 ]. Top goals to achieve malaria eradication include treatment of infected individuals, whether they are symptomatic or not [ 175 ], with the goal of getting rid of all parasite subpopulations (circulating or not), including gametocytes [ 176 ] that transmit the disease to Anopheles mosquitoes where fertilization occurs and a new brood of parasites forms.…”
Section: Twenty-first Century—turning Point In Malaria Researchmentioning
confidence: 99%
“…Indeed, the enormous complexity of this overall system has led to new efforts utilizing mathematical and computational modelling strategies to study the problems and trajectories [ 172 174 ]. Top goals to achieve malaria eradication include treatment of infected individuals, whether they are symptomatic or not [ 175 ], with the goal of getting rid of all parasite subpopulations (circulating or not), including gametocytes [ 176 ] that transmit the disease to Anopheles mosquitoes where fertilization occurs and a new brood of parasites forms.…”
Section: Twenty-first Century—turning Point In Malaria Researchmentioning
confidence: 99%
“…Previous studies have shown that a majority of asexual parasites have AP2-G silenced [47] and this gene silencing may be induced by histone deacetylase (Hda2) [57]. Depletion of HP1 through GDV1, another gene that regulates gametocyte production, was shown to increase schizont development into gametocytes by 50% [47,58]. Further, the presence of Stabilization ligand Shield 1 (Shld1) may also increase transcription of AP2-G by stabilizing the protein complex for transcription and enhance gametocyte production.…”
Section: Gametocyte Commitment and Developmentmentioning
confidence: 99%
“…Additional gametocyte-specific gene discovery efforts have been published ( Ikadai et al, 2013 ; Chawla et al, 2021 ; Muthui et al, 2021 ); although antigen expression, immunization, and TRA assessment of the antibodies are not completed.…”
Section: Novel Tbv Candidate Discovery Directly Using Human Malaria Parasitesmentioning
confidence: 99%